E.07 The role of the neurologist in advanced multiple sclerosis: the patient's perspective. (17th June 2016) - Falet, J; Moore, F; Sigler, G; Al-Jassim, A
Abstract : Background: Few evidence-based disease-modifying treatments exist for progressive multiple sclerosis (MS). How can neurologists best care for patients with advanced MS? Little is known about how patients with progressive MS view their relationship with their treating neurologist, and if the role of the neurologist matches their needs and preferences.Methods: A qualitative cross-sectional analysis of patient preferences regarding the role of the neurologist in their care. Patients with progressive MS and an EDSS score of 6 or more were invited to participate. Patients and caregivers completed separate written questionnaires and were then interviewed by one of the authors. Data were subjected to thematic coding to group common themes and the distribution of themes among different disability sub-groups was analyzed.Results: Full results will be available at the time of the conference. Preliminary results suggest that the neurologist has an important role in updating patients on the progress of their disease and responding to questions. Patients are fearful of becoming dependent on others for their care. The concept of palliative care is unfamiliar to most patients.Conclusions: Despite a lack of disease-modifying treatments for progressive multiple sclerosis, patients believe that the neurologist has an important role in their care.